BUKAN SEKADAR HOME SCHOOLING : RUMAHKU SEKOLAH PERTAMAKU - Khadijah Gani, 1982- Nurkhadijah bt. Ab. Gani (Kuala Lumpur : Telaga Biru Sdn. Bhd, 2017)
Khadijah Gani shares her experiences homeschooling with her children's as inspiration. Parents need to collaborate to ensure homeschooling success.
Contains verses from the Qur'an
Keywords: Child rearing -- Religious aspects -- Islam; Parenting -- Religious aspects -- Islam